International Students and Crime - Forbes-Mewett, H. author. aut Link
IX, 312 p.
Keywords: International students and crime is an issue that impacts on lucrative international student markets, international relations, host countries' reputations, and the security of the broader population. This book presents vital new analyses on international students as victims and perpetrators of crime in Australia, the US and the UK.